Studies on seed and forage yield in 10 populations of sainfoin (Onobrychis saliva) grown as spaced plants and swards - Mohajer, S.; Jafari, A.A.; Taha, R.M. (2011)
In order to study seed and dry matter (DM) yield and relationships between yield and morphological traits, 10 populations of sainfoin (Onobrychis saliva), were assessed in two separate experiments under sward and spaced plant conditions using complete block design with two replications, in Karaj, Iran, during 2004-2007. The data were collected for seed yield, DM yield, plant height, stem number per m(2), flowering date, inflorescences length and 1000-grain weight. The data were analyzed for individual experiment and combined over two experiments. Results showed significant differences among populations for all of traits except 1000-grain weight in sward and DM yield and stem number in spaced plants. Results of combined analysis showed no significant differences among 2 conditions for both seed and DM yield. However, the average values of 7.3 and 6.2 ton ha(-1) DM yield and 337 and 375 kg ha(-1) seed yield were obtained for sward and spaced plants, respectively. Results showed that, populations of Shahrkord and Kashan with average values of 8.08 and 8.06 ton ha(-1) DM yield and Shahrkord with average values 551 kg ha(-1) seed yield had higher production under sward conditions. For spaced plants, Orumieh and Bijar with average values of 7.98 and 7.67 ton ha(-1) DM yield and Bijar and Esfahan with average values of 510 kg ha(-1) seed yield had higher production. Therefore, the populations of Shahrkord and Bijar were introduced as the best ones for both DM and seed production under swards and spaced plants, respectively. DM yield was positively correlated with seed yield, plant height, stem number and inflorescences length, while seed yield had positive and significant relationships with 1000-grain weight, plant height, stem number and inflorescences length. The relationship between spaced plants and swards as measured by phenotypic correlation was poor for all traits except 1000-grain weight. This suggests that response to selection based on spaced plant data would not be reflected in swards, so, for all characters selection should be based on sward yield.